An Andean caracazgo and the peasant society of the seventeenth century: The story of Bartolomé Tupa Hallicalla, curaca de Asillo - Glave, Luis Miguel (1989)
We will not deal here with a common character. The evidence of his performance and his own testimonies show us as someone whose life meant a lot to the lives of many, who were in contact with him or who were not. His social and political practice put him in the most important situations in Peru in the mid-seventeenth century. Precisely, let's take a closer look at his life and his circumstances to understand peasant society, the concrete local relationships and the colonial system in which he played a crossroads role. We will thus understand, once again better, the life of many common people, of the peasants and their organization in the 17th century.